Heterotopias, non-places and other chiasmi (Colloquia Comparativa Litterarum, 2025)
This paper investigates the dichotomy between Dismaland, a dystopian inversion of Disneyland, and Disneyland as an enduring bastion of joyous illusion. Through the lenses of heterotopia, non-places, and chiasmus, it explores how their coexistence authentically grounds one while estranging the other. Banksy's inadvertent use of а chiastic structure in transforming Dismaland is analyzed for its reorganizational logic, and challenging norms. Drawing on Lefebvre, Foucault, Rancière, and Nikolchina, the paper examines cultural representations, spaces, and social relations. The analysis extends to non-places vs. heterotopias, emphasizing Dismaland's resistance to non-place classification. The paper advocates for heterotopias, like Dismaland, to challenge norms and foster alternative cultural production, critiquing interpretations of Situationist theories and proposing Rancière's spatial occupation. The conclusion explores how chiastic structure and heterotopian thinking fuel Dismaland's revolutionary potential, challenging predetermined environments, and underscores art's transformative role in societal evolution towards a renewed existence.
Keywords: Dismaland; Disneyland; heterotopia; dystopia; chiastic structure; non-places